PENINGKATAN KOMPETENSI GURU DALAM MENGEMBANGKAN PEMBELAJARAN KONTEKSTUAL MELALUI TEKNIK MUSYAWARAH GURU MATA PELAJARAN (MGMP ) DI MA. HASYIM ASY’ARI JOMBANG - Fatoni (re-JIEM (Research Journal of Islamic Education Management), 2022)
The government through the ministry of religion has made efforts to improve the quality of education through various programs, including upgrading, curriculum improvement, and so on. However, these efforts still require professional coaching for teachers, with no exception to MA. Hasyim Asyari Jogoroto, Jombang Regency. This research was carried out with the aim of improving teacher competence in planning and implementing contextual learning through the supervision technique of the Subject Teacher Consultation (MGMP). This school action research involved 15 teachers at MA Hasyim Asyari Jogoroto Jombang which was carried out in 2 cycles. Each cycle goes through stages of planning, action, observation and reflection. The technique of supervising discussion is to increase competence in planning and implementing contextual learning from “enough” in cycle 1 to “good” in cycle 2. The average value of teacher competence in planning Contextual Learning in cycle 1 = 75.33 and cycle 2 = 81.83 and The average value of teacher competence in implementing contextual learning in cycle 1 = 74.53 and cycle 2 = 82.40.